Feasibility of radical cardiac‐sparing, treatment planning strategies for patients with locally advanced, non‐small cell lung cancer. Issue 12 (13th October 2022) - Kim, Joshua P.; Dewalt, Jake; Feldman, Aharon; Adil, Khaled; Movsas, Benjamin; Chetty, Indrin J.
Abstract: Purpose: A set of treatment planning strategies were designed and retrospectively implemented for locally advanced, non‐small cell lung cancer (NSCLC) patients in order to minimize cardiac dose without compromising target coverage goals. Methods: Retrospective analysis was performed for 20 NSCLC patients prescribed to 60–66 Gy that received a mean heart dose (MHD) ≥10 Gy. Three planning approaches were designed and implemented. The first was a multi‐isocentric (MI) volume‐modulated arc therapy (VMAT) approach (HEART_MI) with one isocenter located within the tumor and the second chosen up to 10 cm away longitudinally. The second was a noncoplanar (NCP) VMAT approach (HEART_NCP) utilizing up to three large couch angles and a standard arc at couch 0. The final planning strategy took a mixed approach (HEART_HYBRID) utilizing the HEART_NCP strategy for two thirds of the treatment combined with a plan utilizing a pair of opposite‐opposed gantry angles for the remaining treatments. Investigational plans were compared to original plans using dose–volume histogram metrics such as organ volume receiving greater than x Gy ( Vx ) or mean dose ( D mean). Results: Although there was a small but statistically significant decrease in internal target volume coverage for HEART_MI plans and, conversely, a statistically significant increase for HEART_NCP plans, all generated plans met physician‐prescribed target constraints. For heart dose, there were statistically significant decreases in all heart metrics and particularly MHD for the HEART_MI (9.8 vs. 15.4 Gy [ p < 0.001], respectively), HEART_NCP (9.2 vs. 15.4 Gy [ p < 0.001]), respectively), and HEART_HYBRID (7.9 vs. 15.4 Gy [ p < 0.001], respectively) strategies. Conclusions: The strategy providing the best compromise between plan quality and cardiac dose reduction was HEART_NCP, which produced MHD reductions of 37.6% ± 12.9% (6.2 ± 3.4 Gy) relative to original plans. This strategy could potentially reduce adverse cardiac events, leading to improved quality of life for these patients.